IoT System Design for Dragon Fruit Plants Lighting and Watering Automation Using Fuzzy Method - Muhammad Rizqi Maulana; Miftahur Rohman (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2026)
Dragon fruit is a high-value commodity that has gained increasing popularity in the global market, yet requires intensive care, particularly in terms of precise watering and lighting management. In Indonesia, dragon fruit cultivation often faces challenges due to reliance on imprecise manual systems. Conventional systems currently available are frequently inefficient as they cannot dynamically adapt to fluctuating environmental conditions. Therefore, this research aims to develop an IoT-based automation system capable of optimizing dragon fruit growth through intelligent watering and lighting control using more adaptive fuzzy logic methods. The system is designed with an ESP32 microcontroller as the control center, integrated with a YL-69 soil moisture sensor and LDR light sensor. Both sensors were calibrated with high accuracy, showing errors of 2.85% for the moisture sensor and 2.80% for the light sensor respectively. Sensor data is then processed using fuzzy logic to generate proportional control through PWM modulation for water pump and LED light actuators. System implementation demonstrates robust performance, where lights turn on fully at light intensity ≤110 lux, dim at 110-640 lux, and turn off above 640 lux. Meanwhile, the pump operates at maximum capacity when soil moisture ≤45%, at half power between 45-70%, and stops above 70%. The Blynk platform is utilized for real-time environmental monitoring through a user-friendly mobile interface. Twenty-four hours test showed that the system is responsive and adaptive, and has the potential to increase water and energy efficiency compared to conventional systems. Keyword: Dragon Fruit, ESP32, Fuzzy logic, Internet of Things